2022
DOI: 10.1037/pspp0000395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Big Five as an organizing framework for commonly used psychological trait scales.

Abstract: Preliminary results were presented by Timothy F. Bainbridge at the European Conference on Personality, the International Society for the Study of Individual Differences Conference, and at the Australian Conference on Personality and Individual Differences.Supplementary documents and materials, including analysis code and data, can be found on the OSF: osf.io/f9hmg.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 162 publications
(332 reference statements)
2
71
0
Order By: Relevance
“…This model posits that all lower-order personality constructs (e.g., trait aggression) can be appropriately situated under one or more of the five domains (e.g., Lynam & Miller, 2015). Recent empirical work has provided clear evidence that the FFM serves as a clear taxonomy by which lower-order traits (e.g., trait aggression) can be organized (Bainbridge et al, 2021). The traits of the FFM are bipolar in nature, such that a low score on any given personality trait does not simply reflect an absence of that factor, but rather reflects high levels of that trait's opposing end of the spectrum.…”
Section: The Ffm and Trait Aggressionmentioning
confidence: 99%
“…This model posits that all lower-order personality constructs (e.g., trait aggression) can be appropriately situated under one or more of the five domains (e.g., Lynam & Miller, 2015). Recent empirical work has provided clear evidence that the FFM serves as a clear taxonomy by which lower-order traits (e.g., trait aggression) can be organized (Bainbridge et al, 2021). The traits of the FFM are bipolar in nature, such that a low score on any given personality trait does not simply reflect an absence of that factor, but rather reflects high levels of that trait's opposing end of the spectrum.…”
Section: The Ffm and Trait Aggressionmentioning
confidence: 99%
“…Importantly, it has good test-retest reliability (r=.72), which is relevant to our aim of establishing whether facial expressivity correlates with stable traits. Whether it measures global or narrow personality traits (as hinted at by Credé et al, 2016) is of less concern to our aims, in particular given that the majority of commonly-used scales appear to be facets of the Big Five scale (Bainbridge et al, 2022).…”
Section: Results -Manipulation Checks)mentioning
confidence: 99%
“…These questions withstanding, a drastic cleanup of theoretical constructs is required. A recent study showed that tens of constructs about self-concept, self-efficacy, self-esteem, life satisfaction, mindfulness, need for cognition, intellectual engagement, and so forth can be subsumed under the overall scheme of the Big Five factors as expressions of already extant facets (Bainbridge et al, 2022). The evidence discussed here suggests that an even larger reduction is needed in concern to the predictors of school performance.…”
Section: Integrated Cognition-personality-school Performance Modelmentioning
confidence: 99%